2014
DOI: 10.4049/jimmunol.1302238
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cells in the Mucosa of Patients with Inflammatory Bowel Disease Produce Granzyme B and Possess Cytotoxic Activities

Abstract: In both Crohn’s disease (CD) and ulcerative colitis (UC), the gut is massively infiltrated with B cells and plasma cells, but the role of these cell types in the pathogenesis of gut tissue damage remains largely unknown. Human B cells express granzyme B (GrB) when cultured with IL-21, a cytokine overproduced in CD and UC mucosa. We therefore examined whether mucosal B cells express GrB and have cytotoxic activity in inflammatory bowel disease (IBD). GrB-expressing CD19+ and IgA+ cells were seen in the normal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…Administration of DSS for 6 consecutive days led to colitis as evidenced by body weight loss, diarrhea, shortening of the colon, and histopathological alterations, which was greatly ameliorated by Hyp. It has been reported that the overactivation of inflammatory response is a critical mediator associated with the onset of colitis . The concentrations of Hyp in the serum or colonic tissues were greater in Hyp supplementation and Hyp plus DSS co‐treatment groups as compared with that of controls.…”
Section: Discussionmentioning
confidence: 89%
“…Administration of DSS for 6 consecutive days led to colitis as evidenced by body weight loss, diarrhea, shortening of the colon, and histopathological alterations, which was greatly ameliorated by Hyp. It has been reported that the overactivation of inflammatory response is a critical mediator associated with the onset of colitis . The concentrations of Hyp in the serum or colonic tissues were greater in Hyp supplementation and Hyp plus DSS co‐treatment groups as compared with that of controls.…”
Section: Discussionmentioning
confidence: 89%
“…In the current study, it has been shown that CD19 + CD27 + CD38 + plasma cells, the major B cell component in periodontitis tissues, expressed RANKL. Moreover, gut plasma cells in patients with inflammatory bowel disease were demonstrated to be positive for granzyme B (62). However, no granzyme B-positive plasma cells were detected in periodontitis tissues.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude that BAFF may have modulated the anti-tumor activity of B lymphocytes in MDR1A deficiency ex-vivo. Future studies will need to identify the specific B cell subset-derived immune responses against CAC in MDR1A deficiency, which may include several tumoricidal mechanisms, such as production of granzyme B [82] and anti-tumor antibodies [83]. It is possible that colonic MDR1A KO B cells represent the cellular source of enhanced cytotoxic TNFSF10 in the inflamed tumor microenvironment [84].…”
Section: Discussionmentioning
confidence: 99%